A phase I trial and viral clearance study of reovirus (Reolysin) in children with relapsed or refractory extra‐cranial solid tumors: A Children's Oncology Group Phase I Consortium report. Issue 5 (27th February 2015) - Kolb, E . Anders; Sampson, Valerie; Stabley, Deborah; Walter, Alexa; Sol‐Church, Katia; Cripe, Timothy; Hingorani, Pooja; Ahern, Charlotte Hsieh; Weigel, Brenda J.; Zwiebel, James; Blaney, Susan M.
Abstract : Background: Reovirus is a naturally occurring human virus that is cytopathic to malignant cells possessing an activated Ras signaling pathway. We conducted a phase I trial of Reolysin, a manufactured, proprietary isolate of purified reovirus, in children with relapsed/refractory extracranial solid tumors to define the recommended phase 2 dose (RP2D), toxicities, and pharmacokinetic properties when administered as a single agent or in combination with cyclophosphamide. Procedures: Reolysin was administered intravenously for 5 consecutive days, every 28 days. Using a 3 + 3 design, the following dose levels were evaluated: 3 × 10 8 Tissue Culture Inhibitory Dose 50% (TCID50 )/kg; 5 × 10 8 TCID50 /kg (maximum dose was 3 × 10 10 TCID50 ); and 5 × 10 8 TCID50 /kg plus oral cyclophosphamide (50 mg/m 2 /day × 21 days). Results: Twenty‐nine patients were enrolled; 28 were eligible and 24 were evaluable for toxicity and response. There were no hematologic dose‐limiting toxicities. Grade 5 respiratory failure and a Grade 5 thromboembolic event were reported, both in the setting of progressive disease. The median time to clear the reovirus viremia was 6.5 days. Eight of 24 patients were viremic beyond the 5 days of therapy, all were negative by day 17. No patient had detectable viral RNA in saliva or stool. There were no objective responses. Conclusions: Reolysin at a dose of 5 × 10 8 TCID50 /kg daily for 5 days was well tolerated in children alone and in combination with oral cyclophosphamide. Virus was cleared rapidly from the serum and shedding in stool and saliva was not detectable. Pediatr Blood Cancer 2015;62:751–758. © 2015 Wiley Periodicals, Inc.